Kettlebell Exercise Using the Set System Method to Increase Strength Endurance of Shoulder Muscle in Female Wrestling Athletes - Riyatna, Ari Dwi; Berliana, Berliana; Sidik, Dikdik Zafar; Novian, Geraldi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
In the sport of wrestling, a wrestling athlete needs strength endurance in all parts of the body, especially the shoulder muscles which will serve as a starting point for lifting and slamming opponents. But unfortunately, women's wrestling athletes still can't do that, so mistakes often occur. To support this, training with the right guidelines is needed so that the ability to increase physical condition can be achieved efficiently. One model of exercise that is currently popular is the kettlebell training model which has been proven to have various benefits. So this study aims to examine the effect of the kettlebell training model with the set system method on increasing the endurance of the shoulder muscle strength of female wrestling athletes. The experimental method with a randomized pretest-posttest control group design was used in this study. The samples of this study were eight KBB female wrestling athletes who were selected using total sampling from the population, which were then divided into two groups (experimental and control). The instrument used is The Shoulder Endurance Test (SET) which is used to measure the endurance of the shoulder muscle strength. Treatment in the form of a kettlebell exercise model with the set system method was given to the experimental group for eight weeks. Based on the results of the study, it can be concluded that the kettlebell training model with the set system method has a significant effect on increasing the endurance of the female wrestling athletes' shoulder muscle strength. In addition, the kettlebell training model with the set system method provides a greater percentage increase in the endurance of the female wrestling athletes' shoulder muscle strength.